Vállalatok kooperatív magatartása a hazai feldolgozóiparban - Csabina, Zoltán; Leveleki, Magdolna (Szociológiai Szemle, 2024)
Our study attempts to analyse the co-operativeness of Hungarian companies engaged in processing industry. This analysis is based on a representative survey done by the Sociology Department o f the Budapest University of Economics in 1998. We use their database as a resource. The bulk of data sampled by them covered the whole of the processing industry. The 423 companies surveyed are representative of their kind both for their geographical location and size. By co-operativeness we mean - following the definition by Dieter Opp (1996:129) - that „those dealing in the market make a deal according to the prevailing rules valid for the market” . Those labelled „non-co operative” do not necessarily break any criminal code regulations, however, they break some explicit or implicit unwritten laws. In the course of the original survey the questionnaire contained only one cluster of questions concerning norm-keeping/breaking attitudes, and this cluster of questions was about financial etics. They surveyed to what extent did they meet their financial responsibilities. The binary dependent variable acquired this way were compared to partly a set of manifested and partly latent variables come from the factor analysis. The four factors in our interpretation measures: how the companies influence the market, how extensive and profitable their business activities were, how they think about their future prospects. We made comparison to check upon our presumptions on one hand, and on the other hand we wanted to know which of these variables could be used for making a regression model. We checked the correlation of the variables - considering their level of measurement - by using table of contingency, calculating contingency coefficients, X2 statistics, and by using analysis of variance. According to our calculations, only three of the six variables had significant impact on company attitude. These refer to willingness to pay of partners, the structure of ownership and planning prospects. Similarly three of the four latent factors have significant impact on company attitude. The exception is the factor of the extensive growth. At the end of this study we attempt set up a regression model of company attitude. The dependent variable is norm-keeping and norm-breaking attitude while the independent variables are those that proved to influence company attitude. Once the dependent variable is dichotom we use logistic regression model. Data are taken from four nationwide surveys: 1982(N=11,722), I986(N=5,999), 1992(N=2.998) and 1998(N=3792). For testing changes over time equal measures have been constructed in the data-sets, cases have been weighted equally (N=3000/file) and the analysis is performed on a pooled data-set (N=12,000). Changes in social determination of cultural and material life-style are estimated by OLS regression models including the impact of time, that o f the predictor variables, as well as of interaction terms of the predictor variables with time. Although it is assumed on a theoretical basis that social status and life-style have become more crystallized in post-communist Hungary due to increasing market relations and growing social inequalities, the analysis provides little empirical evidence of significant changes in this direction.